The contribution of professional internships to the academic development of engineering and science students: a case study - Gutiérrez-Pulido, Humberto; Orozco-Rodríguez, Claudia (Frontiers in Education, 2025)
IntroductionProfessional internships are widely recognized as a mechanism to bridge the gap between academic training and labor-market demands in science and engineering. However, few studies have comprehensively evaluated students’ perceptions of how internships contribute to their technical and soft-skill development. This study examines the formative impact of the CUCEI (University Center for Exact Sciences and Engineering) internship program at the University of Guadalajara from the students’ perspective.MethodsA 28-item Likert-type questionnaire covering four dimensions—Overall Satisfaction, Practical Experience, Technical Skills, and Soft Skills—was developed and validated. It was administered online to 589 undergraduate interns (60.4% male; 39.6% female). Reliability was evaluated using Cronbach’s alpha (α), and construct validity was examined through exploratory factor analysis; both assessments yielded satisfactory results.ResultsStudents reported high levels of satisfaction, and substantial development of practical experience (85–92% agreement). Practice of specific technical skills was more variable (66-79% “Quite a lot/A lot”), while soft-skill development—especially teamwork, adaptability, and feedback reception—was rated positively (88–90%). Additionally, 37.7% extended their internships, and 45% indicated likelihood of continued employment with their host company.DiscussionFindings confirm that structured internships at CUCEI effectively support student satisfaction and the practical application of academic knowledge, while fostering both technical and interpersonal competencies. Variability in technical-skill opportunities and limited language practice highlight areas for program enhancement. Student feedback underscores the need for deeper industry collaboration and curriculum updates to reinforce hands-on training and global employability.